Efeitos da salinidade sobre o desenvolvimento vegetativo do noni sob duas condições ambientais, na ausência e presença de composto orgânico - Souza, Maria Cristina Martins Ribeiro de (2014)
The salinity and radiation in excess are abiotic stresses that can affect the growth, productivity and plant metabolism. One alternative to minimize the deleterious effects of stress in plants is the use of organic inputs. Despite the intercontinental adaptability of noni plants are still scarce information on alternatives to minimize the effects of stress, these plants on Brazilian soil. The objective of this study was to evaluate the effects of salinity of irrigation water on the initial growth and metabolism of plants noni (Morinda citrifolia L.) grown in two environments, in the absence or presence of organic matter. The statistical design was a randomized block design arranged in split plot scheme, with 5 repetitions. The plots consisted of the cultivation environments (greenhouse and open sky), the subplots salinity levels of irrigation water (ECw: 0.3, 1.5, 3.0, 4.5 and 6.0 dS m-1), and the split were represented by the absence and presence of organic matter. The combination of these factors resulted in 20 treatments, each replicate consisted of three pots (one plant per pot), totaling 300 vessels. To facilitate the description of the results, the thesis is divided into four chapters. The first relates to the development and tolerance, the second gas exchange and morphological changes to the third organic solutes and the membrane damage and fourth mineral nutrition of soil and foliage. The variables used were: Height, dry mass of shoots (DMS), root (DMR), stem (DMS) and leaves (DML) determined at 30, 60, 90 and 110 DAT (Days after treatment application). With data from dried pasta of different plant organs calculated the salinity tolerance of these plants. Moreover, were determined stomatal conductance (gs), net photosynthesis (A), transpiration rate (E), water use efficiency (ratios A/E and A/g), relative chlorophyll content, leaf proline content, soluble protein, N-aminossolúveis and soluble carbohydrates at 60 and 90 DAT. At 110 DAT were determined stem diameter, leaf area, leaf density, degree of leaf succulence, foliar concentrations of calcium, potassium, magnesium, nitrogen, sodium, electrical conductivity of soil saturation extract (CEes), the levels of calcium, magnesium, potassium and sodium. In general, the salinity of irrigation water caused a linear increase in CEs in organic solutes in Ca, Mg, N, Na, Cl and Na/K ratio and the effect observed in the open was more significant than in greenhouse atmosphere. On the other hand, the growth variables, gas exchange and chlorophyll content were decreased with increasing salinity of irrigation water. With regard to tolerance of plants tolerant noni showed moderate tolerance to salinity or when irrigated with water of 1.5 and 3.0 dS m-1, independent of the cultivation environment. A strong interaction between salinity and growth environment for most growth variables, and the noni plants under greenhouse conditions proved tolerant to salinity up to 6.0 dS m-1, which is more suitable environment for seedling production of this crop when irrigated with saline water. If the quality plants attributes are considered it is possible verify that the open sky environment was superior, main to low and moderate values of salinity.